Is the PRGF Living Up to Expectations? - Clements, Benedict (Occasional Papers; Occasional Paper ;, 2002)
In late 1999 the IMF established the Poverty Reduction and Growth Facility (PRGF) to integrate the objectives of poverty reduction and growth more fully into its operations for the poorest countries, and to base these operations on national poverty reduction strategies prepared by the country with broad participation of key stakeholders. A review of the program would be conducted two years later. This paper synthesizes two papers prepared by IMF staff: Review of the Poverty Reduction and Growth Facility: Issues and Options, and Review of the Key Features of the Poverty Reduction and Growth Facility: Staff Analyses. The paper draws on a broad range of internal and external views gathered between July 2001 and February 2002, including discussions at regional forums, meetings with donor government officials and representatives of civil society organizations, and comments of key officials in member countries with PRGF arrangements.